ANALISIS EFEKTIVITAS IMPLEMENTASI CORETAX SEBAGAI SISTEM ADMINISTRASI PAJAK DIGITAL - Novika Adhisty; Acum Wijaya; Alfina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of Coretax implementation as a digital tax administration system in improving the quality of tax services and taxpayer compliance in Indonesia. The research employs a literature review method with a descriptive qualitative approach. The data used are secondary data obtained from scientific journals, official government reports, and publications from relevant international institutions. Data were collected through academic search engines such as Google Scholar, ScienceDirect, and the official portal of the Directorate General of Taxes. The analysis technique was conducted by reviewing, comparing, and synthesizing various previous studies related to the digitalization of tax administration and the implementation of Coretax.